A Method for Assessing the Impact of a Computer-Based Decision Support System on Health Care Outcomes - Bankowitz, R. A.; Lave, J. R.; McNeil, M. A. (Methods of Information in Medicine, 1992)
The wide variation in utilization of diagnostic resources has not been decreased by the proliferation of new diagnostic technologies. We wish to test the hypothesis that the introduction of a medical decision support system into clinical practice could potentially lead to more efficient use of diagnostic information, and therefore lead to a reduction in overall laboratory use and cost of care. We have devised and are currently implementing a randomized controlled trial of a computer based decision support system, the University of Pittsburgh version of Quick Medical Reference (QMR).The main purpose of the study is to determine the effect of the QMR program on specific outcome measures: length of hospital stay, number and types of diagnostic tests ordered, and overall charges. An important part of this evaluation is relating the initial level of diagnostic uncertainty expressed by the admitting housestaff team to utilization of diagnostic resources. The purpose of this paper is to describe the methodology for carrying out this controlled trial, and to describe our initial experiences with its implementation.
Keywords: Computer-Assisted Diagnosis; Differential Diagnosis; Randomized Controlled Trial; Medical Care Evaluation; Outcomes Process and Assessment